2013
DOI: 10.1016/j.chemosphere.2013.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticides and heavy metals in fish from Lake Awassa, Ethiopia: Insights from stable isotope analysis

Abstract: 20The levels and bioaccumulation of organochlorine pesticides (OCPs) and heavy metals 21 were studied in muscle and liver of three fish species, with two trophic levels, from Lake

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 28 publications
3
35
1
2
Order By: Relevance
“…They reflect the input from point and non-point sources of contamination (Yamada et al 2009;Hahladakis et al 2013;Yohannes et al 2013a, b). Properties, such as high toxicity, high stability, high lipophilicity, electrochemical stability, and adsorption to sediments, make PAHs a potentially dangerous group of chemicals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They reflect the input from point and non-point sources of contamination (Yamada et al 2009;Hahladakis et al 2013;Yohannes et al 2013a, b). Properties, such as high toxicity, high stability, high lipophilicity, electrochemical stability, and adsorption to sediments, make PAHs a potentially dangerous group of chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…Lake Awassa and Ziway are found in the Ethiopian Rift Valley. The threats to the lakes are factory effluents, solid and liquid wastes generated by different sectors, small-and large-scale farming, and also sewer lines (Awulachew et al 2007;Yohannes et al 2013a, b). With regard to the status of potentially toxic elements, we recently reported that the sediments collected from the Akaki River was polluted moderate or to a heavy degree by Cr, Zn, and Pb, notpolluted to moderate rate with Ni, and non-polluted by Cu (Mekonnen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В качестве доноров электронов могут выступать важные биологически активные соединения, содержащие атомы N, S и O с парами электронов: белки, аминокислоты, нуклеотиды, нуклеиновые кислоты. Поэтому ионы тяжелых металлов относятся к приоритетным загрязнителям окружающей среды (Yohannes et al, 2013). Содержание тяжелых металлов в тканях рыб -важный показатель экологического состояния населяемого ими водоема.…”
Section: Introductionunclassified
“…According to the EU guidelines the allowable residual limit concentration of OCPs in drinking water is 0.1μg/L (Jansen and Harmsen 2011). Little work has been done on monitoring the residues of OCPs in surface waters in Ethiopia, and most of the studies have concentrated on evaluating the OCP and heavy metals residue levels in big Rift valley lakes like Ziway and Hawasa, focusing on quantifying the residue levels in fish (Abayneh et al 2003;Dsikowitzkyet al 2012;Yohannes et al 2013). Some other studies in Africa examined the status of organochlorine pesticides in freshwater systems, and detected a number of OCPs in water samples (Awofolu and Fatoki 2003;Adeyemi et al 2011).…”
Section: Introductionmentioning
confidence: 99%